Touch imprint cytology and stereotactically-guided core needle biopsy of suspicious breast lesions: 15-year follow-up - Schulz-Wendtland, R.; Fasching, P. A.; Bani, M. R.; Lux, M. P.; Jud, S.; Rauh, C.; Bayer, C.; Wachter, D. L.; Hartmann, A.; Beckmann, M. W.; Uder, M.; Loehberg, C. R. (Senologie - Zeitschrift für Mammadiagnostik und -therapie, 2016)
Introduction: Stereotactically-guided core needle biopsies (CNB) of breast tumours allow histological examination of the tumour without surgery. Touch imprint cytology (TIC) of CNB promises to be useful in providing same-day diagnosis for counselling purposes and for planning future surgery. Having addressed the issue of accuracy of immediate microscopic evaluation of TIC, we wanted to re-examine the usefulness of this procedure in light of the present health care climate of cost containment by incorporating the surgical 15-year follow-up data and outcome.Patients and Methods: From January until December 1996 we performed TIC in core needle biopsies of 173 breast tumours in 169 patients, consisting of 122 malignant and 51 benign tumours. Histology of core needle biopsies was proven by surgical histology in all malignant and in 5 benign tumours. Surgical breast biopsy was not performed in 46 patients with 46 benign lesions, as the histological result from the core needle biopsy and the result of the TIC were in agreement with the suspected diagnosis from the complementary breast diagnostics. A 15-year follow-up of these patients followed in 2013 and follow-up data was collected from 40 women.Results: In the 15-year follow-up of the 40 benign lesions primarily confirmed using CNB and TIC, a diagnostic sensitivity, specificity, positive and negative predictive value and accuracy of 100 % was found.Conclusion: TIC and stereotactically guided CNB showed excellent long-term follow-up in patients with benign breast lesions. The use of TIC to complement CNB can therefore provide immediate cytological diagnosis of breast lesions.
Keywords: breast lesions; breast diagnostics; touch imprint cytology; core-needle biopsy